Potensi Dan Peran Serta Krama Subak Dalam Pengembangan Kawasan Agrowisata Di Kecamatan Mengwi Dan Kuta Utara, Kabupaten Badung - Artaya, I Made Ari; Sugianto, I Made Agus; Manuaba, I Nyoman; Rumiati, I Gusti Ayu Ngurah Lita (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Badung Regency is highly dependent on tourism, while the agricultural sector based on the subak system faces land conversion pressure and declining economic contribution. Integrating agriculture and tourism through subak-based agrotourism development is a strategic approach to sustain agrarian landscapes while improving community welfare. This study aimed to identify the potential of subak areas for agrotourism development and analyze the participation of krama subak (subak members) in Mengwi and North Kuta Districts, Badung Regency. A participatory–spatial approach was applied by combining Participatory Rural Appraisal (PRA) and Analysis of Tourism Operation Areas and Natural Attraction Objects (ADO-DTWA) across 83 subak. The results showed that all subak were categorized as moderately to highly potential, with key strengths in agro-cultural landscape attractiveness, environmental conditions, water availability, and accessibility. Werdhi Putra Sedana and Tegan subak were identified as highly potential due to their diverse attractions, basic facilities, and strong community support. Krama subak demonstrated high participation in cultural preservation, landscape management, educational attractions, and tourism services, although limitations in capacity, facilities, and marketing remain constraints. Spatially, Mengwi functions as the core subak-based agrotourism area, while North Kuta acts as a transitional agrarian–tourism gateway. Sustainable development requires strengthening community capacity, improving facilities, and implementing community-based governance models.